(untitled) (Global Journal of Science Frontier Research, 2021)
People strategy simply aim to establish best practice in each of the HR policy areas there have been attempts to describe people strategy as an internally coherent set of HR policies and practices This endeavor has proven to be both difficult and elusive As one might expect there appears to be no one single ideal type of people strategy with a set of HR policies and practices that can be adopted by organizations seeking to manage their people more strategically Lynda Gratton Catherine Truss 2003 People of a firm is a strategic asset and a very important element and the backbone of every firm Anam Rashi Rad Mizana 2013 People strategy plays a critical role in harmonizing strategic human resource management implementation in an organization Linda Gratten Catherine Truss 2012